Human Intelectin-1 (hITL-1) as Modulator of Metabolic Syndrome (MetS): An In Silico Study - Vishnupriya N; Narayanaswamy Radhakrishnan (Wolters Kluwer Medknow Publications, 2024)
Human intelectin-1 (hITL-1) has been known to be involved in diseases such as asthma, cancer, metabolic disorders, and inflammatory bowel disease. In the present study, we aimed to evaluate hITL-1 as modulator of metabolic syndrome (MetS) using an in silico approach. AQ2 - The eight selected human (h) proteins, namely tumor necrosis factor-alpha (hTNF-alpha), myeloid differentiation primary response protein 88 (hMyD88), toll like-receptor 4 (hTLR4), cyclooxygenase 2 (hCOX 2), vascular cell adhesion molecule 1 (hVCAM 1), nuclear factor kappa B (hNF kappa B), leptin (hleptin), and interleukin 6 (hIL 6), were investigated on the docking analysis of hITL-1 (protein-protein) by using the HDOCK method. Furthermore, physicochemical properties of eight interested proteins were carried out using ProtParam tool. In the present study, two selected proteins, namely hMyD88, hCOX 2, have shown theoretical isoelectric point (PI) values greater than 7.0 which indicates these proteins are basic in nature. The protein-protein docking analysis showed that hNF kappa B exhibited the maximum docking score of -311.95 (kcal/mol) with the target protein hITL 1. Thus, the present find provides a new knowledge in understanding the hITL 1 as modulator of metabolic syndrome.